HUBUNGANMEROKOK DAN PAPARAN POLUSI DENGAN KEJADIAN BRONKITIS - Riyadi, Agung (Politeknik Kesehatan Kemenkes Bengkulu, 2016)
Based on the incidence of bronchitis in hospital Dr.M. Yunus Bengkulu inJanuary-July of 2013 found the incidence of as many as 1,050 cases of bronchitis . Bronchitiscauses and risk factors are smoking , exposure to pollution , infection , heredity , and socialstatus . The results of this survey to be one of the reasons to investigate the associationbetween smoking and exposure to pollution with bronchitis incidence in Polyclinic HospitalLung Dr.M. Yunus Bengkulu 2014 . The study design used was cross sectional . Thispopulation was all patients who came to the Polyclinic Hospital Lung Dr.M. Yunus Bengkulu. The number of samples in this study were 153 patients who were taken with accidentalsampling technique . To examine the relationship between the dependent and independentvariables used chi-square test , with univariate and bivariate analysis. The results showed thatmost of the respondents ( 65.4 % ) who had a habit of smoking and almost sebagiaan ofrespondents ( 29.4 % ) exposed to pollution . Chi-square test analysis on the relationship ofsmoking to the incidence of bronchitis obtained p value = 0.000 means that there is asignificant relationship between the relationship of smoking with the incidence of bronchitis inthe clinic Dr.M Yunus Bengkulu Lung Hospital and the relationship with the incidence ofbronchitis pollution exposure obtained p value = 0.161 means that there is no significantrelationship between exposure to pollution relationship with the incidence of bronchitis in theclinic Lung Hospital Dr.M Yunus Bengkulu. It is expected that the hospital can do counselingand put up posters about the effects of smoking and exposure to pollution with the incidenceof bronchitis in order to decrease the incidence of bronchitis .